Actual tendencies of changes in self-perception of youth in the context of forming social solidarity - Pinchuk, Іhor V.; Derbin, Alexey P. (Journal of the Belarusian State University. Sociology, 2020)
The article discusses current changes in the strategies of behaviour of young citizens, manifested in social atomization. Together with the development of scientific and technological progress, the digitalization of almost all spheres of life, the specifics of modern life style are described. The actualization of the public request for personal emotional satisfaction, self-realization is fixed. In the field of labour relations, attention is focused on the introduction of distance forms of work organization. A hypothesis is being put forward that a guideline on personal development influences the choice of strategies for building marriage and family relations. In aggregate, it is assumed that changing patterns of behaviour at the interpersonal level make it possible to take a different look at the mechanisms for the formation of civil dialogue and social solidarity. The question is raised about the need to build in modern realities an adequate strategy for communication with citizens, including as part of ideological work.
Keywords: self-realization; digitalization; social atomization; virtual space; self-perception; civil dialogue; crowdsourcing; social solidarity